Factor 25r^2-60rd+36d^2

Math
25r2-60rd+36d2
Rewrite 25r2 as (5r)2.
(5r)2-60rd+36d2
Rewrite 36d2 as (6d)2.
(5r)2-60rd+(6d)2
Check the middle term by multiplying 2ab and compare this result with the middle term in the original expression.
2ab=2⋅(5r)⋅(-6d)
Simplify.
2ab=-60rd
Factor using the perfect square trinomial rule a2-2ab+b2=(a-b)2, where a=5r and b=-6d.
(5r-6d)2
Factor 25r^2-60rd+36d^2

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top